Návrh na modernizaci přístrojového vybavení oddělení perinatologie ve VFN v Praze - Rejdová, Petra; Rejdová Petra (České vysoké učení technické v Praze, 2018)
Tato diplomová práce se zabývá návrhem na modernizaci přístrojového vybavení perinatologického oddělení VFN v Praze. Nejprve byla vytvořena situační analýza současně používaného přístrojového vybavení, ze které vzešly nevyhovující technologie. S ohledem na potřeby oddělení byla provedena analýza trhu a managementem VFN byly zvoleny nejvhodnější varianty přístrojů. Pro zvolené přístroje byly identifikovány nákladové položky vstupující do jejich životního cyklu a byl vytvořen výpočet celkových nákladů na vlastnictví těchto přístrojů.

The goal of this diploma thesis is to define the proposal for the modernization of medical devices at Perinatology department GUH in Prague. In the beginning, the situational analysis of the current medical devices was created to define which technologies would be best to be replaced. After this an analysis of the market was created with consideration of their needs. Management of the GUH defined the most appropriate and relevant variants. Costs were identified based on the life-cycle of defined devices. After this, the calculation of the Total Cost of Ownership was created.
The Proposal for the Modernization of Medical Devices at Perinatology Department in General University Hospital in Prague
Keywords: Total Cost of Ownership,čistá současná hodnota,zdravotnické přístroje,nákup zdravotnické techniky,ST analyzátor,resuscitační přístroj; Total Cost of Ownership,net present value,medical devices,the purchase of medical equipment,ST analyzer,resuscitation device